Carbon nitride-based lotus leaf bionic structure photocatalytic material as well as preparation method and antibacterial application thereof
By combining graphite phase carbon nitride with iron ore to form a lotus leaf bionic structure, the problem of small light absorption range and high photogenerating electron recombination rate of graphite phase carbon nitride materials is solved, and efficient photocatalytic antibacterial effect is achieved. Multiple areas show versatility.
Patent Information
- Application Number
- CN202411301490.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-10
AI Technical Summary
The graphite phase carbon nitride material has a small light absorption range and a high recombination rate of photogenerated electrons and holes, resulting in poor antibacterial effects.
The preparation method of carbon nitride-based lotus leaf bionic structure photocatalytic material is adopted. By combining graphite phase carbon nitride with iron ore, a lotus leaf bionic structure is formed, which enhances the light absorption range and reduces the recombination rate of photogenerated electrons and holes. Improve the adsorption capacity of water molecules and oxygen.
It significantly improves the ability of photocatalytic production of reactive oxygen species, effectively kills bacteria, has good antibacterial properties, and has wide application prospects in medical and food industries. It also has a certain removal effect on tetracycline wastewater and nitric oxide gas.
Smart Images

Figure CN119281359A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial materials, and specifically relates to a carbon nitride-based lotus leaf bionic structure photocatalytic material, a preparation method thereof, and an application thereof in antibacterial applications. Background Art
[0002] Bacteria have caused great harm to the food, medical and other industries. How to effectively kill bacteria has become a hot topic of concern. Conventional sterilization methods such as alcohol disinfection, ultraviolet irradiation and high-temperature cooking have the disadvantages of short duration of sterilization effect and high energy consumption. Therefore, finding an efficient and green sterilization technology has become the current research focus.
[0003] Photocatalytic technology is an emerging green and efficient antibacterial technology. Various photocatalysts have been reported. Inorganic metal oxides such as titanium dioxide have certain bactericidal effects, but titanium dioxide only absorbs ultraviolet light, which accounts for 5% of sunlight, and its light absorption rate is not high. Organic reduced semiconductor graphite phase carbon nitride is a new type of antibacterial material with the advantages of a wide source of raw materials and good biocompatibility. The photocatalytic antibacterial effect of graphite phase carbon nitride mainly catalyzes water molecules and oxygen to generate active oxygen species, such as hydroxyl radicals and superoxide radicals. These active oxygen species have extremely strong redox ability and can destroy bacterial cell walls, causing bacterial contents to flow out, thereby achieving the antibacterial purpose. CN202310421061.4 discloses a method for loading nano-copper on graphite phase carbon nitride and synthesizing an antibacterial material with 2,5-furandicarboxylic acid and ethylene glycol ester, but this synthesis method is complicated and costly. CN202211347888.7 discloses a quaternary ammonium salt functionalized graphite phase carbon nitride antibacterial material and a preparation method thereof. However, this method still has the problems of small light absorption range of graphite phase carbon nitride, high recombination rate of photogenerated electrons and holes, and complex preparation method.
[0004] In view of the technical problems of small light absorption range and high recombination rate of photogenerated electrons and holes in graphite phase carbon nitride materials, it is very important to find a simple preparation method to increase the light absorption range of graphite phase carbon nitride, reduce the recombination rate of photogenerated electrons and holes, and improve the antibacterial effect. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a carbon nitride-based lotus leaf bionic structure photocatalytic material and its preparation method and application in antibacterial, so as to solve the technical problems of small light absorption range and high recombination rate of photogenerated electrons and holes in graphite phase carbon nitride materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a carbon nitride-based lotus leaf bionic structure photocatalytic material, comprising the steps of: 1) After melamine, urea and a modifier are mixed and ground evenly, the mixture is calcined, washed and dried to obtain graphite phase carbon nitride; 2) The graphite phase carbon nitride obtained in step 1) is dispersed in deionized water, and then an iron source, an oxidant and a regulator are added, mixed evenly, subjected to hydrothermal reaction, washed, and dried to obtain a carbon nitride-based lotus leaf bionic structure photocatalytic material.
[0007] Preferably, in step 1), the mass percentages of melamine, urea and modifier are (50%~79%): (20%~40%): (1%~10%); the modifier is any one of calcium carbonate, sodium carbonate, potassium carbonate and calcium chloride.
[0008] Preferably, in step 1), the calcination conditions are: heating to 500-600° C. at a heating rate of 10° C. / min, and calcining for 2-4 h.
[0009] Preferably, in step 2), the mass ratio of graphite phase carbon nitride, iron source, oxidant and regulator is 1: (0.05-0.25): (1-10): (0.1-0.5); the mass ratio of graphite phase carbon nitride and deionized water is 1:20.
[0010] Preferably, in step 2), the iron source is any one of ferrous sulfate heptahydrate, ferrous chloride and ferrous nitrate; the oxidant is any one of potassium permanganate, potassium dichromate and ammonium persulfate; and the regulator is any one of sodium hydroxide, sulfuric acid, nitric acid and citric acid.
[0011] Preferably, in step 2), the hydrothermal reaction is carried out at 100-200° C. for 6-12 h.
[0012] Preferably, in step 2), the washing conditions are: washing with deionized water and ethanol alternately, and centrifuging, the centrifugal speed is 8000-10000 rpm, and the centrifugal time is 3-5 minutes.
[0013] Preferably, in step 2), the drying condition is 60-80° C. and the drying time is 6-12 h.
[0014] The present invention also discloses a carbon nitride-based lotus leaf bionic structure photocatalytic material, which is prepared by the above-mentioned preparation method and includes graphite phase carbon nitride and bog iron ore coordinated and connected with the graphite phase carbon nitride through Fe-N bonds, and the mass percentage of bog iron ore and graphite phase carbon nitride is (1.60%-7.01%): 1.
[0015] The invention also discloses the application of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared by the preparation method in antibacterial applications.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a preparation method of a carbon nitride-based lotus leaf bionic structure photocatalytic material. Inspired by the surface structure of lotus leaves in nature, graphite phase carbon nitride and bog iron ore are designed as lotus leaf bionic structures, and graphite phase carbon nitride is used as the substrate of the carbon nitride-based lotus leaf bionic structure photocatalytic material. Combining the advantages of the two materials, a new carbon nitride-based lotus leaf bionic structure photocatalytic material is developed. The obtained carbon nitride-based lotus leaf bionic structure photocatalytic material has a wide light absorption range and a low recombination rate of photogenerated electrons and holes. The construction of the lotus leaf effect structure enhances the adsorption capacity of the composite material for water molecules and oxygen, which is conducive to the photocatalytic generation of active oxygen species. The reaction conditions are mild, the preparation principle is simple, the operation is easy, and it is convenient for industrial production. It has good antibacterial properties against Gram-negative bacteria and positive bacteria, and is expected to be used in medical, food and other industries. It has a certain removal effect on tetracycline wastewater and nitric oxide gas, showing the versatility of the material.
[0017] Furthermore, the mass percentages of melamine, urea and modifier are (50%~79%): (20%~40%): (1%~10%); the modifier is any one of calcium carbonate, sodium carbonate, potassium carbonate and calcium chloride; the prepared graphite phase carbon nitride flakes become thinner and more uniform, and the thermal polymerization reaction of melamine and urea is more complete.
[0018] The present invention also discloses a carbon nitride-based lotus leaf biomimetic structure photocatalytic material obtained by the above-mentioned preparation method. According to the concept of the bionic lotus leaf structure, bog iron ore is hydrothermally synthesized in situ on the surface of graphite phase carbon nitride. The bog iron ore grows in situ on the surface of block graphite phase carbon nitride in the form of nanorods to form a lotus leaf biomimetic structure. The lower layer is block graphite phase carbon nitride, and the surface protrusions are bog iron ore. The protrusion surface is hydrophilic and can adsorb water molecules. There are air cavities between adjacent protrusions, which can adsorb oxygen. Due to the protrusions on the surface of the composite material, there are cavities that can accommodate gas, thereby increasing the water contact angle; due to the cavity, the material's oxygen adsorption capacity is enhanced. In addition, the height of the nanorod protrusions on the surface of the composite material measured by atomic force microscopy is 77nm. The composite material has a large water contact angle and a strong oxygen adsorption capacity. Due to the protrusions on the surface of the lotus leaf effect material, the surface roughness can be increased and the light absorption capacity can be improved. The obtained carbon nitride-based lotus leaf bionic structure photocatalytic material has a larger light absorption range, a low recombination rate of photogenerated electrons and holes, can improve the utilization rate of photogenerated electrons and holes, and enhance the ability to produce hydroxyl radicals and superoxide radicals. These two active oxygen species can effectively kill bacteria and purify water and gas. It has a good antibacterial effect on Escherichia coli and Staphylococcus aureus.
[0019] The present invention also discloses the application of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared by the above-mentioned preparation method in antibacterial treatment; photogenerated electrons and holes react with water molecules and oxygen on the surface of the material to generate active oxygen species such as hydroxyl radicals (·OH) and superoxide radicals (·O2⁻). These active oxygen species have strong oxidizing properties and can destroy the cell wall and cell membrane of bacteria, resulting in bacterial death. Since the material of the present invention has the ability to efficiently generate active oxygen species, it exhibits excellent antibacterial effect. The carbon nitride-based lotus leaf bionic structure photocatalytic material has good antibacterial properties against both Gram-negative bacteria (such as Escherichia coli) and positive bacteria (such as Staphylococcus aureus). This broad-spectrum antibacterial property makes the material have broad application prospects in multiple fields such as medical treatment and food. Compared with traditional antibacterial methods, photocatalytic antibacterial technology has the advantages of environmental protection, high efficiency and sustainability. It does not require additional chemical reagents, and can achieve antibacterial effects by only using light energy, thereby reducing pollution to the environment. In addition, the material can also be recycled, which reduces the cost of use and conforms to the concept of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the X-ray diffraction spectrum of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Figure 2 This is the Fourier transform infrared spectrum of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Figure 3 This is an X-ray photoelectron spectrum of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Figure 4 It is a high-resolution X-ray photoelectron spectrum of the N element of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Figure 5 It is a high-resolution X-ray photoelectron spectrum of the Fe element of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Figure 6 This is a scanning electron microscope image of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Figure 7 This is a static water contact angle diagram of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Figure 8 This is a fitting diagram of the oxygen temperature-programmed chemical adsorption and desorption peak area of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Fig. 9 This is a surface atomic force microscope scanning height map of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Fig.10This is a diagram of the lotus leaf effect mechanism of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Fig.11 This is a diagram of the light absorption range of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Fig.12 This is a photoluminescence spectrum of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Fig.13 This is an electron spin resonance spectrum of hydroxyl radicals generated by the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention under visible light irradiation; Fig.14 This is an electron spin resonance spectrum of superoxide radicals generated by the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention under visible light irradiation; Fig.15 The carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention was irradiated with visible light for 90 minutes to kill Escherichia coli plate culture results; Fig.16 The carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention was irradiated with visible light for 90 minutes to kill Staphylococcus aureus in a plate culture; Fig.17 This is the result of the degradation of tetracycline wastewater by the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention under visible light; Fig.18 This is the result of removing nitric oxide under visible light by the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention; Fig.19 This is the result of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared in Example 2 of the present invention removing nitric oxide and converting it into nitrogen dioxide under visible light. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0022] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0023] The present invention is further described in detail below in conjunction with the accompanying drawings: In nature, the aquatic plant lotus increases the surface roughness of its leaves through tiny protrusions and surface textures, which reduces light reflectivity and improves the light absorption efficiency of the lotus leaves. At the same time, the surface protrusion structure is conducive to improving the ability to adsorb gas and water molecules, thereby providing energy for growth and development through photosynthesis. Based on this idea, a carbon nitride-based photocatalytic material with a lotus leaf surface structure was designed for artificial photosynthesis to generate reactive oxygen species, kill bacteria, and purify water and gases. Graphite phase carbon nitride is low in cost, effective, and non-toxic, making it an ideal lotus leaf effect material substrate.
[0024] Bog iron ore is a mineral widely found in nature. It has the characteristics of cheap raw materials and wide sources. It is also an oxidized semiconductor with narrow band gap and wide light absorption range. Bog iron ore is generally used as industrial desulfurization and water treatment agent. Its morphology is controllable and it is hydrophilic. It is an ideal candidate material for lotus leaf surface protrusions.
[0025] The problem to be solved by the present invention is that the graphite phase carbon nitride material has a small light absorption range, a high recombination rate of photogenerated electrons and holes, and a poor antibacterial effect. To solve this problem, the present invention hydrothermally synthesizes bog iron ore nanorods in situ on the surface of graphite phase carbon nitride according to the concept of a bionic lotus leaf structure. The graphite phase carbon nitride serves as the base of the lotus leaf structure, and the bog iron ore particles serve as the protrusions of the lotus leaf structure, forming a lotus leaf effect structure. The resulting lotus leaf structure photocatalytic material simultaneously forms an S-type heterojunction, the light absorption range becomes larger, the recombination rate of photogenerated electrons and holes is reduced, more oxygen can be adsorbed, and more active oxygen species can be generated, so the material can achieve a better antibacterial effect.
[0026] The first object of the present invention is to provide a carbon nitride-based lotus leaf bionic structure photocatalytic material.
[0027] A carbon nitride-based lotus leaf bionic structure photocatalytic material comprises graphite phase carbon nitride and bog iron ore coordinated and connected to the graphite phase carbon nitride via Fe-N bonds, wherein the mass of the bog iron ore accounts for 1.60% to 7.01% of the mass of the graphite phase carbon nitride.
[0028] This carbon nitride-based photocatalytic material mimics the surface structure of lotus leaves in nature. Bog iron ore grows in situ on the surface of bulk graphite phase carbon nitride in the form of nanorods to form a lotus leaf bionic structure. The lower layer is bulk graphite phase carbon nitride, and the surface protrusions are bog iron ore. The protrusion surface is hydrophilic and can absorb water molecules. There are air cavities between adjacent protrusions, which can absorb oxygen. This unique structural design gives it excellent performance. Due to the use of carbon nitride as a substrate and combined with the lotus leaf bionic structure, the material performs well in photocatalysis and has efficient light absorption and light conversion capabilities.
[0029] The second object of the present invention is to provide a method for preparing a carbon nitride-based lotus leaf bionic structure photocatalytic material, wherein melamine, urea and a modifier are mixed and ground evenly, and then a calcination method is used to prepare graphite phase carbon nitride, and then an iron source, an oxidant and a regulator are used as raw materials to synthesize the carbon nitride-based lotus leaf bionic structure photocatalytic material by a hydrothermal method; the method is specifically implemented according to the following steps: Step 1, weigh a certain amount of melamine, urea and a modifier, mix and grind evenly, and then a calcination method is used to prepare graphite phase carbon nitride to obtain a substrate of the carbon nitride-based lotus leaf bionic structure photocatalytic material. Specifically, the following steps are followed: Step 1.1, taking a certain mass of melamine, urea and a modifier, mixing and grinding them evenly to obtain a white precursor A, wherein melamine accounts for 50% to 79% of the total mass of the precursor A, urea accounts for 20% to 40% of the total mass of the precursor A, and the modifier accounts for 1% to 10% of the total mass of the precursor A. The modifier is one of calcium carbonate, sodium carbonate, potassium carbonate and calcium chloride; Step 1.2, placing the white precursor A in a crucible and placing it in a muffle furnace, calcining at 500-600°C for 2-4 hours at a heating rate of 10°C / min, and obtaining a light yellow solid B after calcination; Step 1.3, the solid B is crushed and washed three times with deionized water at 80° C., and centrifuged and dried to obtain powdered graphite phase carbon nitride.
[0030] Step 2, the mass ratio of graphite phase carbon nitride to iron source, oxidant and regulator is 1: (0.05-0.25): (1-10): (0.1-0.5). Specifically, follow the steps below: Step 2.1, putting the graphite phase carbon nitride powder obtained in step 1 into a beaker, adding a certain amount of deionized water, and magnetically stirring for 60 minutes to obtain solution C, wherein the mass ratio of graphite phase carbon nitride to deionized water is 1:20; Step 2.2, adding an iron source to solution C, and magnetically stirring for 20 minutes to obtain solution D, wherein the iron source is one of ferrous sulfate heptahydrate, ferrous chloride, and ferrous nitrate; Step 2.3, adding an oxidant to solution D, and magnetically stirring for 10 minutes to obtain solution E, wherein the oxidant is one of potassium permanganate, potassium dichromate, and ammonium persulfate; Step 2.4, slowly adding a regulator to solution E, and magnetically stirring for 10 minutes to obtain solution F, wherein the regulator is one of sodium hydroxide (concentration 0.1 M), sulfuric acid (concentration 0.1 M), nitric acid (concentration 0.1 M), and citric acid (concentration 0.1 M); Step 2.5, transfer solution F to a polytetrafluoroethylene-lined autoclave, place the autoclave in a forced air drying oven, set the temperature to 100-200°C, and react for 6-12 hours. After the reaction is completed, wait for the autoclave to cool to room temperature to obtain product G; Step 2.6, washing the product G alternately with deionized water and ethanol, and separating it with a centrifuge at a speed of 8000-10000 rpm for 3-5 minutes to obtain a product H; Step 2.7, placing the product H in a forced air drying oven, setting the temperature to 60-80°C, and drying for 6-12 hours to obtain a brown-yellow powder sample, which is the carbon nitride-based lotus leaf bionic structure photocatalytic material.
[0031] The present invention is inspired by the surface structure of lotus leaves in nature, and designs two materials, graphite phase carbon nitride and bog iron ore, into a lotus leaf effect structure. Combining the advantages of the two materials, a new lotus leaf effect material is developed, and the obtained material has a wide light absorption range and a low recombination rate of photogenerated electrons and holes. The construction of the lotus leaf effect structure in the present invention enhances the adsorption capacity of the composite material for water molecules and oxygen, which is beneficial to the photocatalytic generation of active oxygen species. The material prepared by the present invention has mild reaction conditions, simple preparation principles, easy operation, and is convenient for industrial production. The material prepared by the present invention has good antibacterial properties against Gram-negative bacteria and positive bacteria, and is expected to be used in medical, food and other industries. The material prepared by the present invention has a certain removal effect on tetracycline wastewater and nitric oxide gas, showing the versatility of the material.
[0032] The third object of the present invention is to provide an antibacterial application of a carbon nitride-based lotus leaf biomimetic structure photocatalytic material to kill Gram-negative bacteria under visible light. By imitating the micro-nano structure of the lotus leaf surface, the material significantly increases the surface roughness, thereby improving the light absorption capacity. This enhanced light absorption enables the material to more effectively utilize light energy under illumination, generate more photogenerated electrons and hole pairs, and provide a sufficient energy source for the subsequent antibacterial process.
[0033] The fourth object of the present invention is to provide an antibacterial application of a carbon nitride-based lotus leaf bionic structure photocatalytic material for killing Gram-positive bacteria under visible light. The construction of the lotus leaf bionic structure not only enhances light absorption, but also effectively reduces the recombination rate of photogenerated electrons and holes. The recombination of photogenerated electrons and holes inside the material is a major energy loss pathway in the photocatalytic process. By optimizing the material structure and reducing the recombination process, the utilization rate of photogenerated carriers is improved, thereby enhancing the photocatalytic antibacterial performance of the material.
[0034] In addition to its antibacterial properties, the carbon nitride-based lotus leaf biomimetic structure photocatalytic material also has a certain removal effect on pollutants such as tetracycline wastewater and nitric oxide gas. This multifunctionality makes the material also have potential application value in the field of environmental governance.
[0035] The fifth object of the present invention is to provide a carbon nitride-based lotus leaf bionic structure photocatalytic material for use in purifying water bodies by degrading tetracycline wastewater under visible light. The carbon nitride-based lotus leaf bionic structure photocatalytic material can effectively degrade organic pollutants in tetracycline wastewater under visible light irradiation, converting them into harmless or low-toxic substances, thereby purifying water bodies. Since the material has a lotus leaf bionic structure, the light absorption capacity is enhanced, so that the material has higher photocatalytic activity in the visible light range, and the degradation efficiency of tetracycline wastewater is improved.
[0036] The sixth object of the present invention is to provide a carbon nitride-based lotus leaf bionic structure photocatalytic material for the application of removing nitric oxide under visible light for gas purification. The carbon nitride-based lotus leaf bionic structure photocatalytic material can react with nitric oxide gas under visible light irradiation to convert it into harmless nitrate, thereby purifying the air. Since the material surface has a lotus leaf bionic structure, the adsorption capacity of the gas is increased, making it easier for nitric oxide gas to contact the material surface and undergo a photocatalytic reaction. Visible light is required as an energy source, and no additional heating or high pressure conditions are required to achieve effective removal of nitric oxide gas, with the characteristics of low energy consumption and high efficiency.
[0037] Example 1 A carbon nitride-based lotus leaf bionic structure photocatalytic material (marsh iron ore accounts for 1.60% of the mass ratio of graphite phase carbon nitride) and a preparation method, comprising the following steps: Step 1, weigh a certain amount of melamine, urea and a modifier, mix and grind them evenly, and then prepare graphite phase carbon nitride by calcination to obtain a base of a carbon nitride-based lotus leaf bionic structure photocatalytic material. Specifically, follow the following steps: Step 1.1, 7 g of melamine, 2.5 g of urea and 0.5 g of modifier are mixed and ground evenly to obtain a white precursor A, wherein melamine accounts for 70% of the total mass of precursor A, urea accounts for 25% of the total mass of precursor A, and the modifier accounts for 5% of the total mass of precursor A. The modifier is potassium carbonate; Step 1.2, placing the white precursor A in a crucible and placing it in a muffle furnace, calcining at 500°C for 2 hours at a heating rate of 10°C / min, and obtaining a light yellow solid B after calcination; Step 1.3, wash solid B with 80° C. deionized water for three times, and centrifuge and dry to obtain powdered graphite phase carbon nitride.
[0038] Step 2, the mass ratio of graphite phase carbon nitride to iron source, oxidant and regulator is 1:0.05:1:0.1. Specifically, follow the steps below: Step 2.1, take 1 g of the graphite phase carbon nitride powder obtained in step 1 and put it into a beaker, add 20 g of deionized water, and stir magnetically for 60 minutes to obtain solution C, wherein the mass ratio of graphite phase carbon nitride to deionized water is 1:20; Step 2.2, adding 0.05 g of an iron source to solution C, and magnetically stirring for 20 minutes to obtain solution D, wherein the iron source is ferrous sulfate heptahydrate; Step 2.3, add 1 g of oxidant to solution D, and stir magnetically for 10 minutes to obtain solution E, wherein the oxidant is potassium permanganate; Step 2.4, slowly add 0.1 g of a regulator to solution E, and stir magnetically for 10 minutes to obtain solution F, wherein the regulator is sodium hydroxide (concentration is 0.1 M); Step 2.5, transfer solution F to a polytetrafluoroethylene-lined autoclave, place the autoclave in a forced air drying oven, set the temperature to 100°C, and react for 12 hours. After the reaction is completed, wait for the autoclave to cool to room temperature to obtain product G; Step 2.6, washing the product G with deionized water and ethanol alternately, and separating the product G with a centrifuge at a speed of 8000 rpm for 3 minutes to obtain a product H; Step 2.7, placing the product H in a forced air drying oven, setting the temperature to 60° C., and drying for 6 hours to obtain a brown-yellow powder sample, which is the carbon nitride-based lotus leaf bionic structure photocatalytic material.
[0039] Example 2 A carbon nitride-based lotus leaf bionic structure photocatalytic material (marsh iron ore accounts for 4.21% of the mass ratio of graphite phase carbon nitride) and a preparation method, comprising the following steps: Step 1, weigh a certain amount of melamine, urea and a modifier, mix and grind them evenly, and then prepare graphite phase carbon nitride by calcination to obtain a base of a carbon nitride-based lotus leaf bionic structure photocatalytic material. Specifically, follow the following steps: Step 1.1, 5.5 g of melamine, 4.0 g of urea and 0.5 g of modifier are mixed and ground evenly to obtain a white precursor A, wherein melamine accounts for 55% of the total mass of precursor A, urea accounts for 40% of the total mass of precursor A, and the modifier accounts for 5% of the total mass of precursor A. The modifier is calcium carbonate; Step 1.2, placing the white precursor A in a crucible and placing it in a muffle furnace, calcining at 550°C for 4 hours at a heating rate of 10°C / min, and obtaining a light yellow solid B after calcination; Step 1.3, washing solid B with 80° C. deionized water for three times, and centrifugally drying to obtain graphite phase carbon nitride.
[0040] Step 2, the mass ratio of graphite phase carbon nitride to iron source, oxidant and regulator is 1:0.15:10:0.2. Specifically, follow the steps below: Step 2.1, take 1 g of the graphite phase carbon nitride powder obtained in step 1 and put it into a beaker, add 20 g of deionized water, and stir magnetically for 60 minutes to obtain solution C, wherein the mass ratio of graphite phase carbon nitride to deionized water is 1:20; Step 2.2, adding 0.15 g of an iron source to solution C, and magnetically stirring for 20 minutes to obtain solution D, wherein the iron source is ferrous sulfate heptahydrate; Step 2.3, add 10 g of oxidant to solution D, and stir magnetically for 10 minutes to obtain solution E, wherein the oxidant is potassium dichromate; Step 2.4, slowly add 0.2 g of a regulator to solution E, and stir magnetically for 10 minutes to obtain solution F, wherein the regulator is sulfuric acid (concentration is 0.1 M); Step 2.5, transfer solution F to a polytetrafluoroethylene-lined autoclave, place the autoclave in a forced air drying oven, set the temperature to 150°C, and react for 8 hours. After the reaction is completed, wait for the autoclave to cool to room temperature to obtain product G; Step 2.6, washing the product G with deionized water and ethanol alternately, and separating the product G with a centrifuge at a speed of 10,000 rpm for 4 minutes to obtain a product H; Step 2.7, placing the product H in a forced air drying oven, setting the temperature to 80° C., and drying for 12 hours to obtain a brown-yellow powder sample, which is the carbon nitride-based lotus leaf bionic structure photocatalytic material.
[0041] The structure and performance of the carbon nitride-based lotus leaf biomimetic structure photocatalytic material prepared in Example 2 were analyzed. First, X-ray diffraction spectroscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, ultraviolet visible diffuse reflectance spectroscopy, and photoluminescence spectroscopy were used for analysis. In all the figures, graphite phase carbon nitride was marked as CN, bog iron ore was marked as ZFe, and the carbon nitride-based lotus leaf biomimetic structure photocatalytic material sample prepared in Example 2 was marked as 4.21% ZFe / CN.
[0042] from Figure 1 It can be obtained that the characteristic peaks of CN are (100) and (002), the characteristic peaks of ZFe are (110) and (040), and the diffraction peaks of the composite sample are consistent with the diffraction peaks of graphite phase carbon nitride and bog iron ore, respectively, which can indicate that the composite sample was successfully prepared.
[0043] from Figure 2 It can be obtained that CN is at 810cm -1 、1235-1699cm -1 , 3050-3550cm -1 The signal peaks of ZFe are at 480-624 cm -1 The corresponding peaks are Fe-O functional groups. These peaks can be found in the composite samples, which also shows that bog iron ore and graphite phase carbon nitride are successfully composited.
[0044] from Figure 3 It can be seen that in the X-ray photoelectron spectrum of 4.21% ZFe / CN, characteristic peaks of C, N, Fe, and O can be found, which also proves that the material is completely composite.
[0045] from Figure 4 It can be seen that the peak position of the N 1s high-resolution X-ray photoelectron spectrum of 4.21%ZFe / CN is shifted to the left compared with CN, the binding energy becomes larger, and the electron cloud density decreases, indicating that the electrons of the N atoms on 4.21%ZFe / CN are in an outflow state.
[0046] from Figure 5 It can be seen that the peak position of the N 1s high-resolution X-ray photoelectron spectrum of 4.21% ZFe / CN is shifted to the right compared with ZFe, the binding energy becomes larger, and the electron cloud density increases, indicating that there is electron inflow into the Fe atoms on 4.21% ZFe / CN. Figure 4 and Figure 5 It was concluded that the bog iron ore nanorods grew in situ on the surface of graphitic carbon nitride in the form of Fe-N coordination bonds.
[0047] from Figure 6It can be obtained that bog iron ore grows in situ in the form of nanorods on bulk graphite phase carbon nitride, and the two are closely combined.
[0048] Figure 7 The static water contact angle experiment of the material shows that the water contact angle of the composite material is larger than that of CN and ZFe. At the same time, the water contact angle of the ZFe surface is small, indicating that ZFe has a good adsorption effect on water molecules.
[0049] Figure 8 The fitting area of oxygen temperature-programmed chemical adsorption and desorption peak of the material is shown in the figure. The fitting area of oxygen adsorption peak of the composite material is 2.55 times that of ZFe and 17.85 times that of CN, respectively. This indicates that the oxygen adsorption capacity of the composite material is enhanced.
[0050] pass Fig. 9 The height of the ZFe nanorods grown on the surface of the composite material was measured to be approximately 77 nm. Figure 7 , Figure 8 and Fig. 9 , and combined with Figure 6 , proving the existence of the lotus effect on the surface of the material, the reasons are as follows: first, the composite material has cavities that can hold gas due to the protrusions on the surface, which increases the water contact angle; second, due to the cavities, the material's ability to adsorb oxygen is enhanced. In addition, the atomic force microscope measured the height of the nanorod protrusions on the surface of the composite material to be 77nm.
[0051] Schematic diagram of carbon nitride-based lotus leaf bionic structure photocatalytic material Fig.10 As shown, the lower layer is blocky CN, the surface protrusions are ZFe, the protrusion surface is hydrophilic and can absorb water molecules. There are air cavities between adjacent protrusions, which can absorb oxygen.
[0052] from Fig.11 It can be seen that the light absorption cutoff edge of CN is 460 nm, and the light absorption cutoff edge of ZFe is 600 nm. When ZFe and CN are combined, the light absorption edge of the composite material is increased to 580 nm. This is because the protrusions on the surface of the lotus effect material can increase the surface roughness and improve the light absorption capacity. from Fig.12 It can be seen that after ZFe is composited with CN, the fluorescence emission peak intensity of CN at 464 nm decreases, indicating that the recombination rate of photogenerated electrons and holes in the lotus effect material is low.
[0053] exist Fig.13 and Fig.14 In this study, 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) was used as a probe to detect hydroxyl radicals (·OH) and superoxide radicals (·O2 -The peak intensity of hydroxyl radicals and superoxide radicals produced by carbon nitride-based lotus leaf biomimetic structure photocatalytic materials is greater than that of CN and ZFe, indicating that the material has an enhanced ability to produce hydroxyl radicals and superoxide radicals. These two active oxygen species can effectively kill bacteria and purify water and gas.
[0054] The concentrations of Escherichia coli and Staphylococcus aureus used in the antibacterial experiments were both 10 6 CFU / mL, by co-culturing the catalyst with the bacterial solution, the antibacterial properties of the material can be determined. Fig.15 and Fig.16 It can be found that when the carbon nitride-based lotus leaf bionic structure photocatalytic material is irradiated with visible light for 90 minutes, the number of colonies on the bacterial culture plate is significantly reduced compared with the blank. In addition, the effect of the carbon nitride-based lotus leaf bionic structure photocatalytic material in killing Escherichia coli and Staphylococcus aureus is better than that of graphite phase carbon nitride and ZFe, indicating that the material has an antibacterial effect.
[0055] The wastewater used in the material purification wastewater experiment is tetracycline wastewater with a mass concentration of 10 mg / L. The tetracycline concentration is detected by adding the same mass of material and irradiating with visible light for different time periods to determine the material's degradation performance on tetracycline wastewater. The waste gas used in the material purification gas experiment is low-concentration nitric oxide with a concentration of 700ppb, and it continuously and stably passes through a quartz tube with a catalyst. The concentration of nitric oxide is detected by light to determine the material's waste gas purification effect. Fig.17 and Fig.18 The lotus leaf effect material is effective in purifying tetracycline wastewater and purifying nitric oxide waste gas. As can be seen from the figure, the degradation rate of tetracycline wastewater by carbon nitride-based lotus leaf bionic structure photocatalytic material is 70%, which is higher than CN (50%) and ZFe (55%). The removal effect of nitric oxide by carbon nitride-based lotus leaf bionic structure photocatalytic material is 28%, which is higher than CN (23%) and ZFe (10%). Although the removal rate of nitric oxide by carbon nitride-based lotus leaf bionic structure photocatalytic material is 5% higher than that of CN, Fig.19 It can be obtained that the concentration of nitrogen dioxide generated by the lotus effect material after converting nitric oxide is 63ppb, which is lower than the amount of nitrogen dioxide produced by CN alone (95ppb). The above shows that the lotus effect material is better than single graphite carbon nitride and ZFe in purifying water and gas, indicating that the material has potential application in purifying wastewater and gas.
[0056] Example 3 A carbon nitride-based lotus leaf bionic structure photocatalytic material (marsh iron ore accounts for 7.01% of the mass ratio of graphite phase carbon nitride) and a preparation method, comprising the following steps: Step 1, weigh a certain amount of melamine, urea and a modifier, mix and grind them evenly, and then prepare graphite phase carbon nitride by calcination to obtain a base of a carbon nitride-based lotus leaf bionic structure photocatalytic material. Specifically, follow the following steps: Step 1.1, 5.0 g of melamine, 4.0 g of urea and 1.0 g of modifier are mixed and ground evenly to obtain a white precursor A, wherein melamine accounts for 50% of the total mass of precursor A, urea accounts for 40% of the total mass of precursor A, and the modifier accounts for 10% of the total mass of precursor A. The modifier is sodium carbonate; Step 1.2, placing the white precursor A in a crucible and placing it in a muffle furnace, calcining at 500°C for 4 hours at a heating rate of 10°C / min, and obtaining a light yellow solid B after the calcination; Step 1.3, wash solid B with 80° C. deionized water for three times, and centrifuge and dry to obtain powdered graphite phase carbon nitride.
[0057] Step 2, the mass ratio of graphite phase carbon nitride to iron source, oxidant and regulator is 1:0.10:8:0.25. Specifically, follow the steps below: Step 2.1, take 1 g of the graphite phase carbon nitride powder obtained in step 1 and put it into a beaker, add 20 g of deionized water, and stir magnetically for 60 minutes to obtain solution C, wherein the mass ratio of graphite phase carbon nitride to deionized water is 1:20; Step 2.2, add 0.10 g of iron source to solution C, and stir magnetically for 20 minutes to obtain solution D, wherein the iron source is ferrous chloride; Step 2.3, add 8 g of oxidant to solution D, and stir magnetically for 10 minutes to obtain solution E, wherein the oxidant is potassium dichromate; Step 2.4, slowly add 0.25 g of a regulator to solution E, and stir magnetically for 10 minutes to obtain solution F, wherein the regulator is citric acid (concentration is 0.1 M); Step 2.5, transfer solution F to a polytetrafluoroethylene-lined autoclave, place the autoclave in a forced air drying oven, set the temperature to 200°C, and react for 6 hours. After the reaction is completed, wait for the autoclave to cool to room temperature to obtain product G; Step 2.6, washing the product G with deionized water and ethanol alternately, and separating it with a centrifuge at a speed of 9000 rpm for 5 minutes to obtain a product H; Step 2.7, placing the product H in a forced air drying oven, setting the temperature to 70° C., and drying for 6 hours to obtain a brown-yellow powder sample, which is the carbon nitride-based lotus leaf bionic structure photocatalytic material.
[0058] Example 4 A carbon nitride-based lotus leaf bionic structure photocatalytic material (marsh iron ore accounts for 5.50% of the mass ratio of graphite phase carbon nitride) and a preparation method, comprising the following steps: Step 1, weigh a certain amount of melamine, urea and a modifier, mix and grind them evenly, and then prepare graphite phase carbon nitride by calcination to obtain a base of a carbon nitride-based lotus leaf bionic structure photocatalytic material. Specifically, follow the following steps: Step 1.1, 7.9 g melamine, 2.0 g urea and 0.1 g modifier are mixed and ground evenly to obtain a white precursor A, wherein melamine accounts for 79% of the total mass of the precursor A, urea accounts for 20% of the total mass of the precursor A, and the modifier accounts for 1% of the total mass of the precursor A. The modifier is calcium chloride; Step 1.2, placing the white precursor A in a crucible and placing it in a muffle furnace, calcining at 600°C for 4 hours at a heating rate of 10°C / min, and obtaining a light yellow solid B after the calcination; Step 1.3, wash solid B with 80° C. deionized water for three times, and centrifuge and dry to obtain powdered graphite phase carbon nitride.
[0059] Step 2, the mass ratio of graphite phase carbon nitride to iron source, oxidant and regulator is 1:0.25:10:0.5. Specifically, follow the steps below: Step 2.1, take 1 g of the graphite phase carbon nitride powder obtained in step 1 and put it into a beaker, add 20 g of deionized water, and stir magnetically for 60 minutes to obtain solution C, wherein the mass ratio of graphite phase carbon nitride to deionized water is 1:20; Step 2.2, adding 0.25 g of an iron source to solution C, and magnetically stirring for 20 minutes to obtain solution D, wherein the iron source is ferrous nitrate; Step 2.3, add 10 g of oxidant to solution D, and stir magnetically for 10 minutes to obtain solution E, wherein the oxidant is ammonium persulfate; Step 2.4, slowly add 0.5 g of a regulator to solution E, and stir magnetically for 10 minutes to obtain solution F, wherein the regulator is nitric acid (concentration is 0.1 M); Step 2.5, transfer solution F to a polytetrafluoroethylene-lined autoclave, place the autoclave in a forced air drying oven, set the temperature to 120°C, and react for 12 hours. After the reaction is completed, wait for the autoclave to cool to room temperature to obtain product G; Step 2.6, washing the product G with deionized water and ethanol alternately, and separating the product G with a centrifuge at a speed of 8000 rpm for 3 minutes to obtain a product H; Step 2.7, placing the product H in a forced air drying oven, setting the temperature to 65° C., and drying for 7 hours to obtain a brown-yellow powder sample, which is the carbon nitride-based lotus leaf bionic structure photocatalytic material.
[0060] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a carbon nitride-based lotus leaf bionic structure photocatalytic material, characterized in that: The following steps are involved: 1) After melamine, urea and a modifier are mixed and ground evenly, the mixture is calcined, washed and dried to obtain graphite phase carbon nitride; 2) The graphite phase carbon nitride obtained in step 1) is dispersed in deionized water, and then an iron source, an oxidant and a regulator are added, mixed evenly, subjected to hydrothermal reaction, washed, and dried to obtain a carbon nitride-based lotus leaf bionic structure photocatalytic material.
2. The method for preparing the carbon nitride-based lotus leaf bionic structure photocatalytic material according to claim 1, characterized in that: In step 1), the mass percentages of melamine, urea and modifier are (50%~79%): (20%~40%): (1%~10%); the modifier is any one of calcium carbonate, sodium carbonate, potassium carbonate and calcium chloride.
3. The method for preparing the carbon nitride-based lotus leaf bionic structure photocatalytic material according to claim 1, characterized in that: In step 1), the calcination conditions are: heating to 500-600°C at a heating rate of 10°C / min, and calcining for 2-4 h.
4. The method for preparing the carbon nitride-based lotus leaf bionic structure photocatalytic material according to claim 1, characterized in that: In step 2), the mass ratio of the graphite phase carbon nitride, the iron source, the oxidant and the regulator is 1: (0.05-0.25): (1-10): (0.1-0.5); the mass ratio of the graphite phase carbon nitride and deionized water is 1:
20.
5. The method for preparing the carbon nitride-based lotus leaf bionic structure photocatalytic material according to claim 1, characterized in that: In step 2), the iron source is any one of ferrous sulfate heptahydrate, ferrous chloride and ferrous nitrate; the oxidant is any one of potassium permanganate, potassium dichromate and ammonium persulfate; and the regulator is any one of sodium hydroxide, sulfuric acid, nitric acid and citric acid.
6. The method for preparing the carbon nitride-based lotus leaf bionic structure photocatalytic material according to claim 1, characterized in that: In step 2), the hydrothermal reaction is carried out at 100-200° C. for 6-12 h.
7. The method for preparing the carbon nitride-based lotus leaf bionic structure photocatalytic material according to claim 1, characterized in that: In step 2), the washing conditions are: washing with deionized water and ethanol alternately, and centrifuging, the centrifugal speed is 8000-10000 rpm, and the centrifugal time is 3-5 minutes.
8. The method for preparing the carbon nitride-based lotus leaf bionic structure photocatalytic material according to claim 1, characterized in that: In step 2), the drying condition is 60-80° C. and the drying time is 6-12 h.
9. A carbon nitride-based lotus leaf bionic structure photocatalytic material, characterized in that: The preparation method according to any one of claims 1 to 8 is adopted, comprising graphite phase carbon nitride and bog iron ore coordinated and connected to the graphite phase carbon nitride through Fe-N bonds, wherein the mass percentage of the bog iron ore and the graphite phase carbon nitride is (1.60%-7.01%):
1.
10. Application of the carbon nitride-based lotus leaf bionic structure photocatalytic material prepared by the preparation method according to any one of claims 1 to 8 in antibacterial applications.
Citation Information
Patent Citations
Quaternary ammonium salt functionalized graphite phase carbon nitride antibacterial material as well as preparation method and application thereof
CN115735918A
Preparation method and application of bio-based antibacterial and antiviral functional master batch
CN116444825A